Body weight and eGFR during dulaglutide treatment in type 2 diabetes and moderate‐to‐severe chronic kidney disease (AWARD‐7). Issue 6 (29th March 2019) - Tuttle, Katherine R.; Lakshmanan, Mark C.; Rayner, Brian; Zimmermann, Alan G.; Woodward, Brad; Botros, Fady T.
Abstract : In patients with type 2 dibetes and moderate‐to‐severe chronic kidney disease, dulaglutide treatment led to body weight (BW) loss and lesser eGFR decline compared to insulin glargine. As BW may affect muscle mass, creatinine‐based eGFR can be altered independently of kidney function. Cystatin C‐based eGFR is not affected by muscle mass. The objective of this post‐hoc analysis was to determine whether the lesser eGFR decline with dulaglutide was related to BW loss. Baseline characteristics were similar between treatments ([mean ± SD] age, 64.6 ± 8.6 years; women, 48%; BW, 89.1 ± 17.7 kg; eGFR [CKD‐EPI‐cystatin C] 38 ± 14 mL/min/1.73m 2 ). BW decreased with dulaglutide 1.5 and 0.75 mg and increased with insulin glargine ([LSM change (SE)], −2.66 [0.47] kg and −1.71 [0.45] vs 1.57 [0.43] kg; P < 0.001). Changes in eGFR were not significant with dulaglutide 1.5 and 0.75 mg, but eGFR significantly decreased with insulin glargine (eGFR‐CKD‐EPI‐cystatin C [LSM change (95%CI)], −0.7 [−2.5, 1.0] and −0.7 [−2.4, 1.1] vs −3.3 [−5.1, −1.6] mL/min/1.73 m 2 ; P ≤ 0.037 vs glargine). Changes in BW did not correlate with changes in eGFR‐CKD‐EPI‐cystatin C (r = −0.041; n = 471; P = 0.379) or eGFR‐CKD‐EPI‐creatinine (r = −0.074; n = 473; P = 0.106). In conclusion, the lesser decline in eGFR observed with dulaglutide was not influenced by BW loss.